Stability and safety analysis of statin-loaded nano-films for the treatment of diabetic wound - Rasool, Maria; Alotaibi, Nawaf M.; Sarfraz, Muhammad; Siddique, Muhammad Irfan (Penerbit Universiti Kebangsaan Malaysia, 2024)
Diabetes mellitus (DM) is a metabolic disease that delays the regular stages of the wound’s healing process due to delayed inflammatory stages. Due to foot pressure points, chronic foot wounds are ultimately considered the primary cause of lower leg amputation. Diabetic patients have vascular dysfunction and neuropathy, leading to inadequate oxygen supply to the wound area. Statins have a crucial role in the regulation of angiogenesis that could increase vascular endothelial growth factor (VEGF) synthesis. By offering a localized treatment approach while minimizing systemic side effects associated with oral medication, this study aimed to develop statin-loaded nanofilms to determine their stability and safety among healthy individuals as a potential procedure for diabetic wound healing. Simvastatin (SIM) loaded nanofilms formulations (F1-F10) were prepared using the solvent casting method. The formulation was optimized based on tests such as physical appearance, tensile strength, microscopic photographs, morphology, and drug content uniformity. ICH guidelines were followed to determine various parameters (physical appearances, tensile strength, microscopic photographs, morphology, and drug content uniformity) for six-month stability study at three different storage conditions. Safety analysis of the nanofilms was performed on healthy human skin using the Draize skin irritation test. Results showed F7 formulation was considered an optimized formulation as well as stable through the storage period at 4 ± 2°C, 25 ± 2°C, and 40 ± 2 °C. Furthermore, Primary Irritation Index results (PII was 0 showed no irritation in case and control groups) indicate its safety and biocompatibility to skin. Thus, the optimized statin-loaded nanofilm is stable, safe, and non-toxic, which may be used as a potential diabetic wound healing agent.